Exploiting the performance gains of modern disk drives by enhancing data locality. - Deng, Yuhui (Elsevier, 2009)
Due to the widening performance gap between RAM and disk drives, a large number of I/O optimization methods have been proposed and designed to alleviate the impact of this gap. One of the most effective approaches of improving disk access performance is enhancing data locality. This is because the method could increase the hit ratio of disk cache and reduce the seek time and rotational latency. Disk drives have experienced dramatic development since the first disk drive was announced in 1956. This paper investigates some important characteristics of modern disk drives. Based on the characteristics and the observation that data access on disk drives is highly skewed, the frequently accessed data blocks and the correlated data blocks are clustered into objects and moved to the outer zones of a modern disk drive. The idea attempts to enhance spatial locality, improve the efficiency of aggressive sequential prefetch, and take advantage of Zoned Bit Recording (ZBR). An experimental simulation is employed to investigate the performance gains generated by the enhanced data locality. The performance gains are analyzed by breaking down the disk access time into seek time, rotational latency, data transfer time, and hit ratio of the disk cache. Experimental results provide useful insights into the performance behaviours of a modern disk drive with enhanced data locality.
Keywords: Disk drive; Data locality; Data access pattern; Block correlation; Data migration; Performance